Cloning of the chicken progesterone receptor. - Jeltsch, J M (1986)
Monospecific antibodies directed against the chicken progesterone receptor (PR) form B were used to screen a randomly primed phage lambda gt11 cDNA expression library prepared from size-fractionated chicken oviduct mRNA. Two independent immunoreactive clones, lambda cPR1 and lambda cPR2, were isolated. Antibodies selected from anti-PR form B antiserum on matrices of lambda cPR1 and lambda cPR2 fusion proteins detected two proteins on electrophoretic immunoblots of crude and purified PR preparations. These proteins had the same apparent molecular weights as did PR forms A and B crosslinked with the tritiated progestin R 5020. Thus, lambda cPR1 and lambda cPR2 fusion proteins contain epitopes present in both PR forms A and B. A cDNA clone, lambda cPR3, containing the inserts of both lambda cPR1 and lambda cPR2, was isolated from a randomly primed lambda gt10 oviduct cDNA library, indicating that both cDNA inserts were derived from the same oviduct mRNA. Additional evidence that these cDNAs correspond to PR mRNA was provided by sequencing the lambda cPR3 cDNA insert, since it was found to encode the sequence of three tryptic peptides prepared from purified PR form B. A fourth and a fifth cDNA clone, lambda cPR4 and lambda cPR5, were sequentially isolated from the same lambda gt10 cDNA library beginning with a probe derived from the 3' end of the lambda cPR3 insert. Partial DNA sequencing of lambda cPR4 and lambda cPR5 revealed the presence of a sequence coding for a cysteine-rich domain that is strikingly homologous to the amino acid sequences present in the putative DNA-binding domain of the human and chicken estrogen receptors, human glucocorticoid receptor, and v-erbA gene product of the avian erythroblastosis virus.